2021
DOI: 10.17794/rgn.2021.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controllable and Uncontrollable Parameters on Diamond Wire Cutting Performance Using Statistical Analysis: A Case Study

Abstract: Nowadays, most mining and quarrying industries utilize a diamond wire saw machine for bench cutting operations. This method uses a metal wire or cable assembled by diamond beads to cut the hard stone into large blocks. Many parameters classified into controllable and uncontrollable parameters affect the performance of the diamond wire saw cutting method. The uncontrollable parameters are related to rock engineering properties, and controllable parameters are related to operational aspects and machine performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In most mining machines, regardless of the rock mass excavation mechanism, uniaxial compressive strength has a decisive influence on their efficiency and is an important factor in many rock mass classifications. In this regard, diamond wire saws are not an exception, which is corroborated by previous studies, [6], [7], [8]. The results of the said studies show that the cutting speed and sawing efficiency decrease with increasing strength of the rock being sawn.…”
Section: The Influence Of Rock Properties On the Sawing Efficiency Of...supporting
confidence: 86%
See 4 more Smart Citations
“…In most mining machines, regardless of the rock mass excavation mechanism, uniaxial compressive strength has a decisive influence on their efficiency and is an important factor in many rock mass classifications. In this regard, diamond wire saws are not an exception, which is corroborated by previous studies, [6], [7], [8]. The results of the said studies show that the cutting speed and sawing efficiency decrease with increasing strength of the rock being sawn.…”
Section: The Influence Of Rock Properties On the Sawing Efficiency Of...supporting
confidence: 86%
“…Yilmazkaya and Özcelik 2016 established a significant dependence of the degree of wear of diamond beads and uniaxial compressive strength and a slightly smaller dependence with tensile and impact strength, [21]. They also found that by increasing the abrasiveness value determined according to Böhme, the wear of the beads [6] found that when cutting marble, the wear rate of beads increases with increasing uniaxial compressive strength and hardness determined by the Schmidt hammer, and decreases with increasing abrasion. In addition, they found that an increase in the cutting angle increases the wear of diamond wire, that is, the wear of beads is higher when sawing a horizontal cut than with a vertical cut.…”
Section: Wear Of Diamond Beadsmentioning
confidence: 96%
See 3 more Smart Citations